An experimental comparison of Thiol broth with Brewer's thioglycollate for anaerobic blood cultures. - Shanson, D C (1975)
In a series of simulated blood culture experiments, small inocula of eight different strains of Bacteroides and five strains of anaerobic cocci were added to Difco Thiol broth and Southern Group Brewer's thioglycollate. Both methods enabled all of the strains to be isolated after one to three days' incubation, with the exception of Bacteroides melaninogenicus, and most strains to survive after one week. B. melaninogenicus grew more quickly in Difco Thiol broth than in Southern Group Brewer's whereas three strains of anaerobic cocci were isolated first from Southern Group Brewer's. Difco Thiol broth appears to be a satisfactory alternative to Southern Group Brewer's for the isolation of non-sporing anaerobes likely to be found in the blood.